Realizing strong photon blockade at exceptional points in the weak coupling regime - Li, Zigeng; Li, Xiaomiao; Zhang, Guofeng; Zhong, Xiaolan (Frontiers in Physics, 2023)
We theoretically prove that it is possible to realize strong photon blockade at n-order exceptional points (EPn) in a two quantum emitters (QEs) cavity quantum electrodynamics system (QED) even if the emitter-cavity coupling strength is weak. When the single mode cavity is gain, we show that the ultrastrong single-photon blockade (1PB) emerges at two-order exceptional points (EP2) avoiding the strong nonlinearity of the system. In addition, we first give the pseudo-Hermitian condition for the non-Hermitian cavity QED system and find that the third-order exceptional points (EP3) can be predicted under certain constraints of the parameters. For this case, the pronounced 1PB at EP3 will be triggered. Furthermore, we also consider the usual EP2-enhanced single 1PB existing in the system with or without dipole-dipole interaction (DDI) under the pseudo-Hermitian condition. A striking feature is that the system without DDI can realize more obvious 1PB at EP2 than the case of with DDI. What is important is that both EP2 and EP3 will appear in the weak coupling regime. Our proposal sheds new light on strong EP-engineered photon blockade in weak coupling regime, providing unique platform for making high quantity single photon sources.